“Urip Iku Mung Mampir Ngombe”; Konsep Kebahagiaan Masyarakat Miskin Pesisir Yogyakarta di Era Industrialisasi - Casmini Casmini*; Fauzan Anwar Sandiah (Faculty of Psychology, Universitas Gadjah Mada, 2019)
The study aimed to explore the concept of happiness of the coastal poor in Java. It was conducted using grounded approach through interviewing the poor in coastal D.I. Yogyakarta. Research subjects came from six different coastal areas; Parangtritis, Samas, Baru, Goa Cemara, Kuwaru, and Pandansari. This study used narrative content analysis for four aspects of the discourse that originated from 16 research subjects with the background of farmers, laborers, traders and fishermen; (1) a happy experience, (2) sad or risky experience, (3) sources of happiness, (4) individual interpretation of coastal environment conditions. The results showed that the concept of happiness was strongly associated with the fulfillment of physiological needs and social needs.